mRNA-Expression of KRT5 and KRT20 Defines Distinct Prognostic Subgroups of Muscle-Invasive Urothelial Bladder Cancer Correlating with Histological Variants - Eckstein, Markus; Wirtz, Ralph Markus; Gross-Weege, Matthias; Breyer, Johannes; Otto, Wolfgang; Stoehr, Robert; Sikic, Danijel; Keck, Bastian; Eidt, Sebastian; Burger, Maximilian; Bolenz, Christian; Nitschke, Katja; et al. (International Journal of Molecular Sciences, 2018)
Recently, muscle-invasive bladder cancer (MIBC) has been subclassified by gene expression profiling, with a substantial impact on therapy response and patient outcome. We tested whether these complex molecular subtypes of MIBC can be determined by mRNA detection of keratin 5 (KRT5) and keratin 20 (KRT20). Reverse transcriptase quantitative polymerase chain reaction (RT-qPCR) was applied to quantify gene expression of KRT5 and KRT20 using TaqMan (R)-based assays in 122 curatively treated MIBC patients (median age 68.0 years). Furthermore, in silico analysis of the MD Anderson Cancer Center (MDACC) cohort (GSE48277 + GSE47993) was performed. High expression of KRT5 and low expression of KRT20 were associated with significantly improved recurrence-free survival (RFS) and disease-specific survival disease specific survival (DSS: 5-year DSS for KRT5 high: 58%; 5-year DSS for KRT20 high: 29%). KRT5 and KRT20 were associated with rates of lymphovascular invasion and lymphonodal metastasis. The combination of KRT5 and KRT20 allowed identification of patients with a very poor prognosis (KRT20(+)/KRT5(-), 5-year DSS 0%, p < 0.0001). In silico analysis of the independent MDACC cohorts revealed congruent results (5-year DSS for KRT20 low vs. high: 84% vs. 40%, p = 0.042). High KRT20-expressing tumors as well as KRT20(+)/KRT- tumors were significantly enriched with aggressive urothelial carcinoma variants (micropapillary, plasmacytoid, nested).
EVALuna2:35878